PENGARUH PENGGUNAAN METODE SOROGAN TERHADAP KEMAMPUAN MEMBACA KITAB KUNING SANTRI IBTIDA DI PONDOK PESANTREN AL-IHYA SUMEDANG UTARA - Dindin Saefudin; Hadi Hasan Shobaruddin (Al - Mujaddid: Jurnal Ilmu-ilmu Agama, 2021)
The sorogan method is a traditional teaching and learning method that is often used in Islamic boarding schools in Indonesia. This method involves teaching teachers and students face to face and there is a question and answer interaction between the teacher and the students regarding the extent of the students’ ability to understand the lesson, between the abilities of the students. The priority in most existing Islamic boarding schools is the ability to read the Yellow Book. This learning starts from the beginner santri class or often called santri ibtida. Then the author wanted to research the extent of the influence of the sorogan method on the reading ability of the Ibtida students’ Yellow Book using quantitative correlational research methods. As a reference or problem formulation, the author will find out about how the sorogan method is used, the ability to read the yellow book, and the influence of using the sorogan method on the ability to read the yellow book of ibtida students at a nearby Islamic boarding school. As a place for research, the author chose the Al-Ihya Islamic boarding school in North Sumedang, where there is an ibtida class. The author found that there were around 30% of the students who were not yet able to read the yellow book correctly and the other 70% were starting to be able to, students who had started to be able to read this. Dominated by female students, because they often carry out sorogan when they are in the dormitory with their senior students. Therefore, the author is interested in researching the effect of the sorogan method on the reading ability of the Ibtida students. Hopefully this research can be useful as educational information and become a reference for implementing the appropriate sorogan method, especially at the Al-Ihya Islamic boarding school, North Sumedang